27 Neurodevelopmental Outcomes of Preterm Infants Born <29 weeks with Bronchopulmonary Dysplasia Associated Pulmonary Hypertension: A Multicenter Study. (21st October 2022) - Thomas, Soumya; Jain, Sunil; Murthy, Prashanth; Joseph, Chacko; Soraisham, Amuchou; Tang, Selphee; Dosani, Aliyah; Lodha, Abhay
Abstract: Background: More than 1 in 4 preterm infants with bronchopulmonary dysplasia (BPD) develop BPD-associated pulmonary hypertension (BPD-PH) that is associated with significant morbidity. Data regarding neurodevelopmental outcomes with BPD-PH in preterm infants are lacking. Objectives: To determine neurodevelopmental outcomes of preterm infants born < 29 weeks gestational age (GA) with BPD associated pulmonary hypertension at 18 to 24 months corrected gestational age (CGA). Design/Methods: In this retrospective cohort study, preterm infants born < 29 weeks GA between January 2016 and December 2019 at level 3 Neonatal Intensive Care Units at Foothills Hospital in Calgary and the University of Texas Medical Branch (UTMB) in Galveston, who were evaluated at 18-24 months CGA in the neonatal follow-up clinics were included. We compared demographic factors, neurodevelopmental status including Bayley-III scores and sensory impairments between the two groups based on the presence of PH at 36 weeks CGA: Group I: BPD with PH and Group II: BPD without PH, using univariate and multivariable regression models. The primary outcome was a composite of death or neurodevelopmental impairments (NDI). NDI was defined as any cerebral palsy (GMFCS≥1), Bayley-III score < 85 on one or more of the cognitive, motor, or language composite scores, sensorineural or mixed hearing impairment or unilateral or bilateral visual impairment. Results: Of 372 eligible infants, 118 (Group I [BPD-PH] =7, Group II [BPD with no PH] =111) were lost to follow up. Of the remaining 254 infants, 52 in Group I and 202 in Group II were followed at 18-24 months CGA. Group I and Group II had median (IQR) birth weight of 710g (323) and 815g (314) [p=0.004] and median gestational ages (IQR) were 25 weeks (2) and 26 weeks (2) [p=0.020], respectively . Rates of associated impairments are shown in Figure 1. Infants in BPD-PH group (Group I) were more likely to have mortality or NDI (adjusted Odds Ratio [aOR] 3.82; 95% CI: 1.17-12.41) (Table 1). Conclusion: BPD-PH in preterm infants born < 29 weeks GA is associated with increased odds of the composite outcome of death or neurodevelopmental impairment and language delay at 18-24 months CGA.